Modeling the mechanical response of polymers and nano‐filled polymers: Effects of porosity and fillers content. Issue 47 (30th June 2020) - Alasfar, Reema; Ahzi, Saïd; Wang, Kui; Barth, Nicolas
Abstract: In this study, models are developed to predict the mechanical behavior of porous polymer‐based membranes, since they are exposed to temperature and pressure load under service conditions. To the best of our knowledge, existing studies related to numerical simulations of mechanical behavior of polymer nanocomposites do not explicitly report porosity in the modeling. Hence, the proposed models attempt to explicitly examine the effect of porosity. The first model predicts the elastic modulus of porous polymer nanocomposites which is based on Weibull statistical analysis. The results show the combined effects of fillers content and porosity on the modulus. The second model predicts the yield stress for porous polymer nanocomposites. The coupled effects of fillers content and porosity on the yield stress is examined via our proposed extension of the cooperative model. A parametric study is conducted to show the influence of a single parameter used to model the influence of porosity. Abstract :